The Verse of “Career Women” in Qur’an and¬ Their Impact on Harmony and Education in the Family - et. al., Khalik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research was to described the perception of women career of the Al-Qur’an of surah An-Nisa verse 34 and the impact of harmony in families. Being a career woman, has its own problems because of two demands at the same time, namely the demands of career and demands in the family. This research was conducted using a descriptive methodology approach and literature study (librarrarry research) This study has been previously started to 30 women career. The data has been evaluated by quantitatively and qualitatively approach (mixed methods). A qualitative approach is practice to explicate the woman officers' career opinion to Surah An-Nisa verse 34, even though the quantitative approach is used to designate the grade of harmony of women family. For quantitative data, we use the interview. Based on the study and discussion, it can be concluded that: (1) the career woman (Muslim) perceives or believes that the Qur'an, surah An-Nisa verse 34 which is only related to male leadership in the context of worship, especially worship and in the house stairs. Therefore, women's career officials see that their position in public office is not contradictory to the verse, (2) the harmony of women household career officers in general including the harmonious family. This level of harmony is in the "moderate" category, which means there are some indicators of family harmony that are not attained in female career female officials. Nevertheless, given the career women officers have big responsibilities, both related to their work and with their household, career women need to do strategic things in order to increase family harmonization.